Transfection Methods - Ruedel, A.; Bosserhoff, A. K. (Transfection Methods, 2012)
It is an important method in molecular biology to up- or downregulate gene expression in cells. By transfection with expression constructs or silencing RNAs, the functionon genes can be defined and cellular reactions can be analyzed. For this purpose several methods are known and used to date. This article illustrates the most common protocols to introduce DNA or RNA into cells, including lipofection and electroporation. In the case of lipofection the nucleic acid is encapsulated in liposomes which fuse with the cell membrane, thereby releasing the nucleic acid into the cell. Cell division is required for DNA to get into the nucleus to be transcribed. In contrast to that, electroporation utilizes electrical pulses to create small pores in the cell membrane. This method allows transfection directly into the nucleus and therefore does not require cell division. Taken together, all methods can be used for cell transfection but it always has to be tested experimentally which method works best for each cell type. © 2012, Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Arthritis; Cancer; Cell culture; Epithelial cells; Gene expression; Gene silencing; Human; Mesenchymal cells; miRNA; Mouse; Plasmids; Recombinant gene expression; siRNA; Transcription; Transfection; Translation; Tumor cells; Wound-healing